How do I prove the following identity?
cosx (secx - cscx) = 1 - cotx
For the left side, I am at:
cosx (1/cosx - 1/sinx)
Am I anywhere near being right so far? Or is there an easier way to simplify the identity?
hi there ) we are now at that leeson.,and I am proud to say that I'm able to answer your question..and I have an easier way to answer it..here it is:
cos (sec-csc) = 1-cot (start at the left side)
cos sec - cos csc = 1-cot (distribute)
cos(1/cos) - sin/tan(1/sin) = 1-cot (cancel cos and sin)
1-1/tan = 1-cot
1-cot = 1-cot
and that's it!!!
At first, I am also confused with that..but I keep on researching until I learned it!!! hehe..
I hope that I helped you..
O_o